2009
DOI: 10.1080/02656730902856116
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia classic commentary: ‘A randomized clinical trial of radiation therapy versus thermoradiotherapy in stage IIIB cervical carcinoma’ by Yoko Harima,International Journal of Hyperthermia2001;17:97–105

Abstract: In our classic paper, we investigated both the clinical response and survival of patients treated with radiotherapy (RT) or thermoradiotherapy (TRT; RT plus hyperthermia [HT]) for Stage IIIB cervical carcinomas. Our study clearly demonstrated that TRT can result in beneficial effects for complete response and/or local relapse-free survival. To date, six randomized trials including our study have been published on the additive effect of HT in patients with locally advanced cervical cancer. In contrast, the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As such, it was reprinted in the IJH in 2009 [2] accompanied with a "hyperthermia classic commentary" of the key researchers Y. Harima and S. Sawada. They concluded that "our study clearly demonstrated that TRT can result in beneficial effects for complete response and/or local relapse-free survival" [3]. Preparing a systematic review of hyperthermia in the treatment of LACC, [4] we performed a thorough data appraisal, including a comprehensive bias analysis and recalculation of each parameter reported in the original trials (if possible).…”
Section: Letter To the Editormentioning
confidence: 99%
“…As such, it was reprinted in the IJH in 2009 [2] accompanied with a "hyperthermia classic commentary" of the key researchers Y. Harima and S. Sawada. They concluded that "our study clearly demonstrated that TRT can result in beneficial effects for complete response and/or local relapse-free survival" [3]. Preparing a systematic review of hyperthermia in the treatment of LACC, [4] we performed a thorough data appraisal, including a comprehensive bias analysis and recalculation of each parameter reported in the original trials (if possible).…”
Section: Letter To the Editormentioning
confidence: 99%